2013
DOI: 10.1002/app.39718
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of electrospun sulfonated poly(phthalazinone ether ketone) mats as potential matrix of reinforced proton exchange membranes

Abstract: In this paper, the sulfonated poly(phthalazinone ether ketone) (SPPEK) nanofibers with low sulfonation degree are fabricated by electrospinning for the first time. The optimized concentration of SPPEK for electrospinning is 0.16 g ml 21 and the suitable solvent is the mixture of DMAc and NMP. The resulting SPPEK nanofibers show smooth surfaces and uniform diameters of about 50 nm. Proton conductivities of the SPPEK mat and membrane are tested and compared. The result indicates that the proton conductivity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…These results are in agreement with the literature, 62,64 where it is found that the proton conductivity of SPEEK nanober mat is nearly ve times as high as that of the SPEEK composite membrane. Our result is also consistent with the work of Hongwei et al, 62 where two possible pathways are presented: (1) the long-range proton conductivity pathways are formed inside of the nanobers, 65 and (2) the long-range proton conductivity pathways are formed on the surfaces of the nanobers.…”
Section: 9supporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with the literature, 62,64 where it is found that the proton conductivity of SPEEK nanober mat is nearly ve times as high as that of the SPEEK composite membrane. Our result is also consistent with the work of Hongwei et al, 62 where two possible pathways are presented: (1) the long-range proton conductivity pathways are formed inside of the nanobers, 65 and (2) the long-range proton conductivity pathways are formed on the surfaces of the nanobers.…”
Section: 9supporting
confidence: 93%
“…From these results, we can observe that the proton conduction mechanism is more efficient through the surface of the SPEEK-PVB nanobers than through the matrix of SPEEK-PVA; similar results have been observed in other nanocomposites. 61,62 On the other hand, it is possible to observe a critical thickness as a function of the electrospinning time (M-12 with 12 hours of electrospinning time of SPEEK-PVB) where the protonic conductivity is the highest, as shown in Fig. 5a.…”
mentioning
confidence: 98%
“…Then, apparently, reduction of surface concentration of water molecules and sulfonic acid groups on the SPEEK-30%PVB nanofibers strongly affects their conductivity properties as a consequence of a more limited proton conduction via the water-sulfonic acid association. This conclusion about conductivity preferentially taking place on the nanofibers surface would be in agreement with those reported in other studies [32,63]. Moreover, this explanation can be supported by the fact that nanofiber axis orientation is perpendicular to the proton conduction direction, which might difficult conductivity through the nanofiber bulk but on the nanofiber surface.…”
Section: Proton Conductivitysupporting
confidence: 92%
“…Two proton conduction mechanisms associated to the nanofiber morphology could explain this large increment of proton conductivity. On one side, conductivity may be improved through the bulk due to an induced preferential orientation of the ionic channels along the nanofiber axis, and on the other side, conductivity may be encouraged on the nanofiber surface through the strong interface formed between water molecules and external sulfonic acid groups [32].…”
Section: Proton Conductivitymentioning
confidence: 99%
See 1 more Smart Citation